THE ROLE OF WESTERN MAINSTREAM MEDIA: HOW ISLAM IS BEING BRANDED AS PROMOTER OF VIOLENCE - Al Mannan, Md; Shamrir Al-Af, Shah (PEOPLE: International Journal of Social Sciences, 2017)
Whenever we see any terrorist incident committed by a Muslim, happened anywhere in the world, instantly some of the newspapers and TV channels start screaming that it’s a ‘Jihadist’ activity. Jihad has become the synonym of Islamic Terrorism. The western media tries to portray that through Jihad, Islam is encouraging its followers to kill non-believers and people from other religion. This paper is a research on the rise of Islamophobia in the contemporary world and the role of media in spreading it. This wave of anti-Islam sentiment is prevalent in various forms in all the spheres of life but here the ones related with media are emphasized. Here in this paper discussion has been done as to how the media is portraying Islam as the religion which promotes violence and the Muslims as terrorists and ultimately playing a significant role in the global rise of Islamophobia and Xenophobic attack against Muslims. It is important to analyze the role of the media because there is a nexus among Islamophobia-Radicalization-Social marginalization- Security threat. The research contains review of the cases where the media has been biased against Muslims and the further condemnation of this biasedness by the media itself and the views of the expertise thinkers in this field.